2020
DOI: 10.3390/jcm9123956
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Corneal Neuropathy

Abstract: Diabetic keratopathy (DK) is a common, but underdiagnosed, ocular complication of diabetes mellitus (DM) that has a significant economic burden. It is characterised by progressive damage of corneal nerves, due to DM-induced chronic hyperglycaemia and its associated metabolic changes. With advances in corneal nerve imaging and quantitative analytic tools, studies have shown that the severity of diabetic corneal neuropathy correlates with the status of diabetic peripheral neuropathy. The corneal nerve plexus is,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 137 publications
3
49
0
Order By: Relevance
“…Diabetes type 1 and 2 produces corneal tissue complications such as decreased corneal epithelial turnover, less tear production, delayed corneal wounds repair, diminishes corneal surface sensitivity, and even generates neuropathy symptoms [ 34 , 35 ]. Enkephalin levels are elevated in the serum of diabetic type 1 humans and animals, and the levels seemed to be consistent with hyperglycemia and time of evolution [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes type 1 and 2 produces corneal tissue complications such as decreased corneal epithelial turnover, less tear production, delayed corneal wounds repair, diminishes corneal surface sensitivity, and even generates neuropathy symptoms [ 34 , 35 ]. Enkephalin levels are elevated in the serum of diabetic type 1 humans and animals, and the levels seemed to be consistent with hyperglycemia and time of evolution [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study conducted by Alise et al showed that the degree of reduced corneal sensitivity in adult patients with DM was positively correlated with the severity of dry eye (17). The possible mechanisms involved may be that high-level glycosylated end metabolites may cause metabolic damage to the peripheral corneal nerve (18) and thus, reduce the corneal perceptual sensitivity and tear secretion in patients with DM (19)(20)(21). Additionally, corneal perception is positively correlated with blink reflex (22,23) and the decrease in blink reflex can accelerate tear evaporation and lead to an increase in tear osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…DM is a common systemic disease with rising prevalence (Markoulli et al, 2018). Disorders caused by DM are a serious public health challenge and financial burden to many countries (Mansoor et al, 2020). As a complication induced by DM, DK has gained increasing attention recently, and can lead to delayed corneal epithelium and nerve regeneration (Li et al, 2020a;Wang et al, 2020a;Li et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%